Perceptions of Inmates on Social Work Intervention in Osun State Prisons, Nigeria - Akinyemi, Eyitayo Olufunmilayo (American International Journal of Social Science Research, 2019)
The study investigated the inmates on social work intervention in Osun State prisons, Nigeria. The specific objectives of the study identified the age range of the inmates, inmates’ perception towards a societal valued life, level of engagement in skill acquisition and formal education, attitude of government and prison service employees towards inmates’ reformation. The study adopted descriptive research design. The sample consisted of 88 inmates randomly selected from the 880 inmates and eight (8) warders from Ilesa prison yard. The research instrument was a close ended questionnaire and focus group discussion. Data obtained were analysed using percentages and frequency counts. Results showed that inmates’ ages range mostly between 21 and 25 years. Findings also showed inmates perceived they could still live a good and societal acceptable life; the societal services rendered to them were good to an extent that they had positive attitudes towards skill acquisition and formal education; inmates were satisfied with the services rendered by prison workers and welfare provisions from the government. Findings concluded that the inmates believed they could still live an acceptable life during and as an ex-convict. The study recommended that individual inmate could be tailored and encouraged on the need to better their lives in the prison yard and become acceptable and self-reliant ex-convict.